Programming Video Games for the Evil Genius - Cinnamon, Ian (New York McGraw-Hill, 2008)
An awesome mix of racing, board, shoot 'em up, strategy, retro, and puzzle games for the beginning to advanced Evil Genius game creator.
Include Figures and Index.
Keywords: Video games--Design -- Computer games--Design -- Computer games--Programming